2016
DOI: 10.3233/jad-151197
|View full text |Cite
|
Sign up to set email alerts
|

Brain Atrophy of Secondary REM-Sleep Behavior Disorder in Neurodegenerative Disease

Abstract: Background Rapid eye movement sleep behavior disorder (RBD) may present as an early manifestation of an evolving neurodegenerative disorder with alpha-synucleinopathy. Objective We investigated that dementia with RBD might show distinctive cortical atrophic patterns. Methods A total of 31 patients with idiopathic Parkinson’s disease (IPD), 23 with clinically probable Alzheimer’s disease (AD), and 36 healthy controls participated in this study. Patients with AD and IPD were divided into two groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Some researchers successively explored structure changes in PD-RBD patients using voxel-based morphometry, diffusion tensor imaging and structural correlation network methods. They found PD-RBD has decreased volume in more or less cortical and subcortical structures such as thalamus, hippocampus, and cingulate cortex (6)(7)(8)(9)(10)(11)(12). In addition to brain structure, a few researchers also used the resting-state functional MRI (rs-fMRI) to search changes of brain function in PD-RBD.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers successively explored structure changes in PD-RBD patients using voxel-based morphometry, diffusion tensor imaging and structural correlation network methods. They found PD-RBD has decreased volume in more or less cortical and subcortical structures such as thalamus, hippocampus, and cingulate cortex (6)(7)(8)(9)(10)(11)(12). In addition to brain structure, a few researchers also used the resting-state functional MRI (rs-fMRI) to search changes of brain function in PD-RBD.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have used voxel-based morphometry (VBM) to investigate RBD-related gray matter abnormalities in PD, with the most consistent finding being volume loss in the temporal lobes but with other findings including change in the cingulate cortex, posterior regions, and thalamus [7][8][9][10][11]. Another study used deformation-based morphometry (DBM), a technique shown to detect volume changes occurring in PD with better accuracy [12], and found abnormal volume in several cortical (anterior cingulate, olfactory areas) and subcortical (brainstem, cerebellum, thalamus, putamen, amygdala) regions in people with PD with RBD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another study used deformation-based morphometry (DBM), a technique shown to detect volume changes occurring in PD with better accuracy [12], and found abnormal volume in several cortical (anterior cingulate, olfactory areas) and subcortical (brainstem, cerebellum, thalamus, putamen, amygdala) regions in people with PD with RBD [13]. However, these studies have some methodological limitations, notably the use of screening questionnaires for RBD diagnosis [10,11,13], the use of statistical thresholds uncorrected for multiple comparisons [8,10,11], and absence of a healthy control group [10]. Furthermore, the techniques (VBM or DBM) used for analysis were limited by voxel-based resolution, resulting in a partial overview of structural abnormalities in this population.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that RBD is associated with changes in brain morphology similar to those found with OSA, namely cortical thinning in the frontal, temporal, and parietal cortices and the hippocampal region [187]. Earlier studies observed volume loss in the temporal lobes, cingulate, thalamus, and posterior regions of patients with PD and RBD [188][189][190][191]. However, most of these studies lacked a robust diagnostic method for RBD and comparisons with healthy controls.…”
Section: Impact Of Rem Behavior Disorder On Pd Manifestations and Osamentioning
confidence: 99%